Digital Gamification Strategies for Pedagogical Mediation in the Technical Specialty of Executive Secretariat - Navarro Ovares, Carolina (2025)
This article stems from a research project aimed at enriching and diversifyingthe pedagogical mediation strategies used in the ExecutiveSecretariat technical program offered by the Ministry of Public Educationof Costa Rica. This academic program is multidisciplinary in nature and,for that reason, requires diverse learning experiences. In this context, thestudy seeks to answer the following question: Which digital gamificationstrategies are relevant for the pedagogical mediation of the ExecutiveSecretariat technical specialty? To address this, a qualitative study wasconducted using a phenomenological, descriptive design. Data werecollected through a qualitative survey, employing a questionnaire as theprimary instrument. Among the main findings, both teachers and studentsacknowledged the value of digital gamification in the teaching of Executive Secretariat; however, its implementation is hindered by barriers such aslimited resources. The results led to significant conclusions, including theidentification that the program’s content is well-suited to be approachedthrough playful and digital methods, as teachers believe they can beeasily adapted to gamified activities.